Engineered yeast and microalgae mutualisms: Synthetic ecology applied to species isolated from winery wastewater - Simpson, Zoe Faith (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.